Optimasi Search Engine Optimization Dalam Strategi Digital Marketing Untuk Meningkatkan Penjualan Polis Asuransi Syariah - Selfiani, Dwi; Nasution, Muhammad Irwan Padli; Bi Rahmani, Nur Ahmadi (Jurnal Manajerial, 2024)
Background – This study examines how Search Engine Optimization (SEO) can increase sales of sharia insurance policies at Prudential Rantau Prapat Aim – To find out how SEO optimization can be used as part of a digital marketing strategy to increase sales of sharia insurance policies at Prudential Rantau Prapat. Design/ Methodology/ Approach – This study uses a qualitative method with a case study approach and SWOT analysis to identify the strengths, weaknesses, opportunities, and threats faced by businesses when implementing an SEO strategy. Findings – The results of the study indicate that the right SEO strategy can be an effective tool in digital marketing to increase sales of sharia insurance. Although there are challenges such as limited SEO knowledge and technical complexity, great opportunities such as the growth of internet users and the increasing need for sharia insurance can be utilized. Conclusion – Based on the results of the SWOT analysis, the researcher recommends a WO (Weaknesses – Opportunities) strategy. WO strategy: Overcoming weaknesses by taking advantage of opportunities. At this time, companies can invest in SEO training and skills development for the organization, as well as take advantage of opportunities from digital expansion to more effectively reach new audiences. Research Implications – This study provides insights for insurance companies to develop more effective digital marketing strategies. Research Limitations – This study is limited to one case study for Prudential Rantau Prapat.